From Data to Value: Leveraging Business Analytics for Sustainable Management Practices - Hossain, Sazzat; Karim, Farhana; Sultana, Sharmin; Uddin, Mukther; Ahmed, Md Kamal; Chy, Md Аsikur Rаhmаn; Rahman, Habiba; Manik, Mia Md Tofayel Gonee (Journal of Posthumanism, 2025)
The research explores how business analytics supports sustainable management by aligning organizational objectives with sustainable development goals. It highlights the importance of environmental and social responsibilities for organizations. Business analytics provides valuable insights by turning collected data into actionable value. The study uses online survey data and case study analysis to analyze secondary data from industries like manufacturing, retailing, and energy. The research shows that business analytics helps organizations understand process weaknesses and improve operational sustainability by eliminating or minimizing waste. By bridging the gap between data and actionable value generation, business analytics helps organizations meet international sustainability standards and contribute to sustainable management.